Production of bioactive cytokines using plant expression system for cardiovascular cell differentiation from human pluripotent stem cells - Kozue Murata; Kanae Takamura; Risa Watanabe; Akitomo Nagashima; Miho Miyauchi; Yoshiteru Miyauchi; Hidetoshi Masumoto (Stem Cell Research & Therapy, 2025)
Abstract Bioactive cytokines such as vascular endothelial growth factor (VEGF) and Activin A are critical for the differentiation of stem cells into vascular endothelial cells and cardiomyocytes. However, production of the cytokines using conventional Escherichia coli or mammalian cell expression systems carries risks of immunogenicity and viral contamination. In this study, we developed a VEGF and Activin A plant expression system and demonstrated that plant-expressed VEGF and Activin A are as active as their commercial counterparts. We also showed that plant-expressed VEGF and Activin A are as efficient as human recombinant counterparts in inducing endothelial cells and cardiomyocytes from human pluripotent stem cells. These results suggest that plant-expressed VEGF and Activin A are promising alternatives for the safe and efficient production of cardiac cells, specifically cardiomyocytes and endothelial cells, for stem cell-based regenerative medicine.